Audit committee characteristics and financial reporting quality in Nigeria : the mediating effect of audit quality - Bala, Hussaini (2019)
This study examines the mediating effect of audit quality (AQ) proxied by audit fees and Big 4 auditors on the relationship between the audit committee (AC) characteristics and financial reporting quality (FRQ) of listed companies in Nigeria. The study employed 88 firms listed in the Nigerian Stock Exchange through 440 firm-year observations for five years ranging from 2012 to 2016. A multiple regression was employed to test the mediation using the Baron and Kenny and Sobel Tests. The findings reveal that the AC size, AC independence, AC financial accounting experts (ACFAEs), AC legal experts (ACLEs), female AC members (FACMs), AC stock ownership (ACSO), and AC tenure are negatively and significantly associated with the discretionary accruals (DA) and income smoothing (IS) behaviour of firms. In contrast, it is documented that the AC chair cannot be relied upon in minimising agency problems in a situation where the committee is chaired by a shareholder. The study shows that the AC size, AC independence, ACFAEs, ACLEs, and ACSO are positively related to AQ. It is established that AC meetings, FACMs, AC tenure, and AC chair are inversely related to AQ. It is also established that a higher audit fee is associated with lower DA and lower IS. Moreover, the mediation model reveals that audit fees partially and significantly mediate the relationships amongst the AC size, ACFAEs, ACLEs, FACMs, ACSO, and FRQ. This study recommends that the Nigerian SEC should, in the review of subsequent codes, recognise the presence of independent directors and legal experts in the AC as they are found to be effective monitors in constraining artificial smoothing. However, the regulators should be cautious about shareholders serving as chairpersons of the AC, and emphasis should be placed on the financial expertise and experience rather than relying on the status of the shareholders.